PRZEKŁADY LITERATUR SŁOWIAŃSKICH. Tom 1, część 1, Wybory translatorskie 1990–2006. Pod redakcją: Bożeny Tokarz: Katowice: Wydawnictwo Uniwersytetu Śląskiego, 2009. 336 s. - Wojtoń, Regina (Slavia Centralis, 2020)
Review: PRZEKŁADY LITERATUR SŁOWIAŃSKICH. Tom 1, część 1, Wybory translatorskie 1990–2006 In 2009, the first part of the first volume of the scientific journal Przekłady Literatur Słowiańskich (Translations of Slavic Literatures) was published, which is described by Regina Wojtoń in the present article.